Hormonal Effect on Mandarin Orange (Citrus reticulata Blanco) Micro-propagation - Amgai, Resham Babu; Prasai, Hari Kumar; Pandey, Yama Raj (Nepal Journal of Biotechnology, 2016)
Tissue culture is the best option to produce disease free seedling of the fruit crop rapidly. Micro-propagation and use of the in-vitro grafting (micro-grafting) is very helpful for production of virus free planting materials in mandarin. Different levels of the in-vitro hormone affect the success of callusing, shooting and plant regeneration in mandarin. Shoot bud, flower bud and in-vitro seedling epicotyl was used as explants to study the hormonal effect on mandarin micro-propagation. Similarly, 10 levels of BAP and IAA combination on MS media for mandarin tissue culture were used. Observation was done for 100 test tubes per treatment combination after 4, 8 and 12 weeks of culture. Data was arc sine transformed for analysis. Shooting from explants was significantly higher (71.72%) on medium level of the BAP (0.5 mg/L) and IAA (0.2 mg/L) using in-vitro seedling stem as explant, however, it was 27.91% for stem bud as explant. Stem bud showed higher level of callusing (6.15%, p<0.001) in mandarin orange. However, flower bud didn’t develop shoot in mandarin tissue culture. Increment of the in-vitro regeneration of the shooting and callusing was observed by the increment of the in-vitro incubation duration in mandarin orange tissue culture.